Interface engineering improves the performance of green perovskite light-emitting diodes. Issue 8 (26th January 2022) - Guo, Ming-Lei; Lu, Yu; Cai, Xiao-Yi; Shen, Yang; Qian, Xiao-Yan; Ren, Hao; Li, Yan-Qing; Wang, Wen-Jun; Tang, Jian-Xin
Abstract : A facile and reliable crystallization manipulation strategy has been proposed to enhance the radiative recombination and carrier transport capacity of the perovskite layer by modifying the underneath substrate with ammonium thiocyanate. The EQE of PeLEDs is boosted from 3.2% to 14.7%. Abstract : To realize high-performance perovskite light-emitting diodes (PeLEDs), the underlying charge transport layer plays a vital role in charge injection and perovskite growth. Herein, a rational interface engineering method has been proposed to enhance the interfacial crystallization of perovskite films and simultaneously suppress the nor-radiative recombination of excitons by modifying the poly(3, 4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) hole transport layer with ammonium thiocyanate (AT). The morphological control of the perovskite film with the improved crystal orientation arises from the strong interfacial chemical force between AT and perovskite, which promotes enhanced radiative recombination. The optimized PeLEDs achieve a peak external quantum efficiency of 14.7% and current efficiency of 45.4 cd A −1, which are approximately 4.6 times and 4.5 times higher than the control device, respectively.